Psychological advocacy toward healing (PATH): study protocol for a randomized controlled trial - Brierley, Gwen (BioMed Central, 2013)
BACKGROUND: Domestic violence and abuse (DVA), defined as threatening behavior or abuse by adults who are intimate partners or family members, is a key public health and clinical priority. The prevalence of DVA in the United Kingdom and worldwide is high, and its impact on physical and mental health is detrimental and persistent. There is currently little support within healthcare settings for women experiencing DVA. Psychological problems in particular may be difficult to manage outside specialist services, as conventional forms of therapy such as counseling that do not address the violence may be ineffective or even harmful. The aim of this study is to assess the overall effectiveness and cost-effectiveness of a novel psychological intervention tailored specifically for survivors of DVA and delivered by domestic violence advocates based in third-sector organizations. METHODS AND STUDY DESIGN: This study is an open, pragmatic, parallel group, individually randomized controlled trial. Women ages 16 years and older experiencing domestic violence are being enrolled and randomly allocated to receive usual DVA agency advocacy support (control) or usual DVA agency support plus psychological intervention (intervention). Those in the intervention group will receive eight specialist psychological advocacy (SPA) sessions weekly or fortnightly, with two follow-up sessions, 1 month and then 3 months later. This will be in addition to any advocacy support sessions each woman receives. Women in the control group will receive usual DVA agency support but no additional SPA sessions. The aim is to recruit 250 women to reach the target sample size. The primary outcomes are psychological well-being and depression severity at 1 yr from baseline, as measured by the Clinical Outcomes in Routine Evaluation–Outcome Measure (CORE-OM) and the Patient Health Questionnaire (PHQ-9), respectively. Secondary outcome measures include anxiety, posttraumatic stress, severity and frequency of abuse, quality of life and cost-effectiveness of the intervention. Data from a subsample of women in both groups will contribute to a nested qualitative study with repeat interviews during the year of follow-up. DISCUSSION: This study will contribute to the evidence base for management of the psychological needs of women experiencing DVA. The findings will have important implications for healthcare commissioners and providers, as well as third sector specialist DVA agencies providing services to this client group. TRIAL REGISTRATION: ISRCTN58561170